Effect of Saliva pH on Shear Bond Strength of Orthodontic Brackets - Mohammad Hossein Toodehzaeim; Elham Khanpayeh (Tehran University of Medical Sciences, 2015)
Objectives: The purpose of this study was to evaluate the effect of salivary pH on the shear bond strength (SBS) of orthodontic brackets to tooth surface. Materials and Methods: Eighty intact premolars were randomly divided into four groups of 20.  After bonding a bracket on each tooth, the groups one to four were stored in artificial saliva at a pH of 3.8, 4.8, 5.8, and 6.8, respectively for two months. The artificial saliva solutions were refreshed weekly. Each tooth was then embedded in an acrylic block so that the crown was exposed and its buccal surface was parallel to the direction of the force during SBS testing. All brackets were debonded using Dartec universal testing machine, and the mean values of SBS in different groups were compared using one-way analysis of variance (ANOVA).  Results: The mean SBS value in group 1 (pH 3.8) was significantly lower than that in other groups (P value<0.05). The differences between other groups were not sig- nificant (P>0.05). Conclusion: Decreased salivary pH, due to poor oral hygiene, and/or frequent con- sumption of acidic beverages, may be responsible for orthodontic bracket bond fail- ure.